2019
DOI: 10.1002/jemt.23254
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of efficacy of the self‐assembling peptide‐based remineralization agent on artificial enamel lesions

Abstract: The objective of this in vitro study was to analyze and compare the biomimetic remineralizing efficacy of the self-assembling peptide (P11-4) with agents containing casein phoshopeptideamorhous calcium phosphate fluoride (CPP-ACFP) and sodium fluoride (NaF) on artificial caries lesions using DIAGNOdent and micro-computed tomography (μCT). Artificial enamel lesions were prepared on extracted impacted sound mandibular third molars. The samples were randomly allocated to four groups (n = 8): Group 1, P11-4 (Curod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 35 publications
2
24
0
1
Order By: Relevance
“…On the other hand, although the fluorescence loss and lesion area were decreased linearly, Duraphat did not significantly differ in enamel remineralization at 7, 14, and 21 days from the baseline. Since this result also supports previous researches [6,23] that showed the low remineralization potential of the Duraphat varnish for the longer duration, conventional fluoride varnish can be recommended to be applied more frequently.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…On the other hand, although the fluorescence loss and lesion area were decreased linearly, Duraphat did not significantly differ in enamel remineralization at 7, 14, and 21 days from the baseline. Since this result also supports previous researches [6,23] that showed the low remineralization potential of the Duraphat varnish for the longer duration, conventional fluoride varnish can be recommended to be applied more frequently.…”
Section: Discussionsupporting
confidence: 89%
“…The changes in the samples of the control group from baseline to day 21 suggest that some natural remineralization of WSLs occurred. Previous studies [23,25] determined that the artificial saliva solution, which is frequently used as a negative control group in in vitro studies, displayed remineralizing potential for WSLs. Therefore, the decrease in fluorescence loss and lesion area can be contributed to the daily renewal of the artificial saliva at pH range between 6.5 and 6.8 throughout the whole present trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For SAP P 11 -4 to be translated into daily clinical practice, it is essential that clinicians can visualize the treatment effect with available diagnostics. Both ex vivo and in vivo studies have reported the successful use of laser fluorescence, PTR-LUM, Impedance, QLF and radiography in monitoring remineralization after SAP P 11 -4 application in a time-dependent manner 12,13,[16][17][18][19][20] .…”
mentioning
confidence: 99%
“…This β-sheet forming self-assembling peptide possesses anionic groups in the side chains that attract Ca 2+ ions, diffuses well into the body of the caries lesions due to its low viscosity, and triggers self-assembly within the lesion inducing the precipitation of HA in situ. A single application of P11-4 improves the appearance of white spot lesions after 180 days in a small-scale clinical study (Alkilzy et al, 2018a;González-Cabezas and Fernández, 2018;Arifa et al, 2019;Jablonski-Momeni et al, 2019;Üstün and Aktören, 2019;Kamal et al, 2020;Li et al, 2020). However, more evidence is still needed before this peptide can be used in caries prevention and regular therapy (Alkilzy et al, 2018a;González-Cabezas and Fernández, 2018;Arifa et al, 2019;Jablonski-Momeni et al, 2019;Üstün and Aktören, 2019;Kamal et al, 2020;Li et al, 2020).…”
Section: Self-assembled Peptidesmentioning
confidence: 99%